(3eG jMJGL Edjg GdUGfY ef CYeGd GdgfOSIs - (3GdHhRLGfj, CHh GdhaGA, eMeO Hf eMeO Hf jMji Hf ESeGYjd, (B388 (3g`s
(3ChdgG (B:s
(3HSe Gddg fJPGcQ HMVQJg GdYGdjI ef GdCYeGd GdgfOSjI GdJj jcKQ GSJYeGdgG YfO GdUfGY eLQOG ef GdYdd hGdHQGgjf jSgd Ydi GUfGY JfGhdg hjbQH Ydjge WQjbJg hLYdJ GdcJGH KdGKI YTQ HGHGs
(3BNQgG (B:s
(3eJSGhjGJ GdCVdGY hGdRhGjG hbSefG cd VdY ef CVdGYg GdKdGKI CbSGe eJSGhjI hQSefG Ydi ehGVY GdCbSGe bSeG ef OhGFQ YXGe ajKSe GdcQI hgPg UhQJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\21s
(3cTa GdXfhf (B2\1472s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs